Insulin resistance and high molecular weight adiponectin in obese and non-obese patients with Polycystic Ovarian Syndrome (PCOS) - Farnaz Kamali Haghighi Shirazi; Zohre Khodamoradi; Marjan Jeddi (BMC Endocrine Disorders, 2021)
Abstract Background Polycystic ovarian syndrome (PCOS) is the most common endocrinopathy among young women. Insulin resistance is a key feature in the pathogenesis of PCOS; also high molecular weight adiponectin is a marker of insulin resistance. The aim of this study was to evaluate the insulin resistance, metabolic and androgenic profiles and high molecular weight adiponectin in obese and non-obese PCOS patients. Methods In this cross-sectional study in outpatient endocrinology clinics of Shiraz University of Medical Sciences, 80 women aged 17–43 years old with PCOS were enrolled. Biochemical and hormonal assay was done on fasting blood sample on the third day of follicular phase. Results The individuals had a mean age of 28.39 ± 6.56 years, mean weight of 65.41 ± 12.59 Kg, mean BMI of 25.5 ± 4.9, and mean waist circumference of 88.0 ± 13.1 cm. Of all individuals 20% had frank insulin resistance with HOMA-IR > 3.8. Although the obese PCOS patients had lower levels of high molecular weight adiponectin (P = 0.03) than the normal weight PCOS individuals, the level of insulin and insulin resistance was not different in them (P = 0.13, 0.13). Patients with classic PCOS phenotype significantly had higher levels of insulin resistance and free androgen index (P < 0.001, 0.001). We found a significant correlation between the insulin level and free androgen index (correlation coefficient: 0.266 and P = 0.018) after adjusting for BMI. Conclusion This cross-sectional study showed a high incidence of insulin resistance in PCOS patients independent of obesity, and determined BMI related lower level of high molecular weight adiponectin in obese PCOS individuals. More detailed studies are warranted for evaluation of insulin resistance and its pathophysiologic role in PCOS.